A dual band shorted triangular patch antenna for vehicular application. Issue 10 (10th July 2021) - Chakrabarti, Satyajit; Chakraborty, Ashim
Abstract: This reports the development of a dual port linearly polarized shorted triangular patch antenna for C‐ and J‐band with improved bandwidth and decoupled ports. Two orthogonal shorted walls and perforation on the patch have been conceived for improved bandwidth. L‐probe has been adopted to produce linear polarizations (LP). The shorted walls conceived on the equilateral triangular patch achieve higher compactness. The perforation in addition to the shorted wall enforces an overlapping response of the TM10, TM11, TM20 and slot modes resulting in an improved bandwidth. The slot mode and the TM10 mode overlap at the lower band. The TM11 and TM20 modes coupled together at the upper band. At the C‐band, it exhibits bandwidth ≥12.4%. Impedance bandwidth ≥36.4% with an isolation ≥23 dB is realized at the J‐band ports. It capitulates very stable gain of about 5 dBi at the lower band. At the upper band gain ≥7 dBi over 10–13 GHz is achieved and the maximum is 8.5 dBi. These gains are due to half of the equilateral triangular patch only. All these results are superior to the earlier reported investigations. Dual port communication ability is the enhance feature of the antenna.